Millipore xMap® Luminex (HATMAG-68K): An Accurate and Cost-Effective Method for Evaluating Alzheimer's Biomarkers in Cerebrospinal Fluid - Hansen, Erika Oliveira; Dias, Natalia Silva; Burgos, Ivonne Carolina Bolaños; Costa, Monica Vieira; Carvalho, Andréa Teixeira; Teixeira, Antonio Lucio; Barbosa, Izabela Guimarães; Santos, Lorena Aline Valu; Rosa, Daniela Valadão Freitas; Ribeiro, Aloisio Joaquim Freitas; Viana, Bernardo Mattos; Bicalho, Maria Aparecida Camargos (Frontiers in Psychiatry, 2021)
Background: Alzheimer's disease (AD) biomarkers are of great relevance in clinical research, especially after the AT(N) framework. They enable early diagnosis, disease staging and research with new promising drugs, monitoring therapeutic response. However, the high cost and low availability of the most well-known methods limits their use in low and medium-income countries. In this context, Millipore xMap® Luminex may be a cost-effective alternative. In our study, using INNOTEST® as reference, we assess the diagnostic accuracy of Millipore xMap® and propose a cutoff point for AD. Methods: We performed lumbar puncture of seven older individuals with clinically defined AD, 17 with amnestic mild cognitive impairment (aMCI) and 11 without objective cognitive impairment-control group (CG). Cerebrospinal fluid (CSF) biomarkers concentrations for aB42, p-Tau, and t-Tau were measured by INNOTEST® and Millipore xMap®, and then the techniques were compared to assess the diagnostic accuracy of the new test and to define a cutoff. Results: INNOTEST® and Millipore xMap® measurements showed all correlations >0.8 for the same biomarker, except for t-Tau that was 0.66. Millipore xMap® measurements showed a robust accuracy for all biomarkers, with AUC higher than 0.808 (t-Tau), and the best for Aβ42 (AUC = 0.952). The most accurate cutoffs were found at 1012.98 pg/ml (Aβ42), 64.54 pg/ml (p-tau), 3251.81 pg/ml (t-tau), 3.370 (t-Tau/Aβ42), and 0.059 (p-Tau/Aβ42). Conclusion: Given its good accuracy and cost-effectiveness, Milliplex xMap® tests seems a reliable and promising tool, especially for low and middle-income countries.